EGMR 25181/94 vom 25. August 1998 , CASE OF HERTEL v. SWITZERLAND - Hudoc Ch (1998)
Violation of Art. 10;Not necessary to examine Art. 6-1;Not necessary to examine Art. 8;Pecuniary damage - claim dismissed;Costs and expenses partial award - domestic proceedings;Costs and expenses partial award - Convention proceedings; Violation: 10